Intricate Regulatory Mechanisms of the Anaphase-Promoting Complex/Cyclosome and Its Role in Chromatin Regulation - Bodrug, Tatyana; Welsh, Kaeli A.; Hinkle, Megan; Emanuele, Michael J.; Brown, Nicholas G. (Frontiers in Cell and Developmental Biology, 2021)
The ubiquitin (Ub)-proteasome system is vital to nearly every biological process in eukaryotes. Specifically, the conjugation of Ub to target proteins by Ub ligases, such as the Anaphase-Promoting Complex/Cyclosome (APC/C), is paramount for cell cycle transitions as it leads to the irreversible destruction of cell cycle regulators by the proteasome. Through this activity, the RING Ub ligase APC/C governs mitosis, G1, and numerous aspects of neurobiology. Pioneering cryo-EM, biochemical reconstitution, and cell-based studies have illuminated many aspects of the conformational dynamics of this large, multi-subunit complex and the sophisticated regulation of APC/C function. More recent studies have revealed new mechanisms that selectively dictate APC/C activity and explore additional pathways that are controlled by APC/C-mediated ubiquitination, including an intimate relationship with chromatin regulation. These tasks go beyond the traditional cell cycle role historically ascribed to the APC/C. Here, we review these novel findings, examine the mechanistic implications of APC/C regulation, and discuss the role of the APC/C in previously unappreciated signaling pathways.